A certificação ISO 9000 e o desempenho financeiro das companhias abertas brasileiras - Rodrigues, Francisco Carlos Tadeu Starke (2008)
The evidences that the quality management practices contribute positively to the financial performance of a firm do not produce a consensus. It is important to take off the impression ISO 9000 is so popular that it could not deserve more intense and effective academic production; there are many effects promoted by the introduction of this standard at the organizational level in brazilian companies and they were not yet well studied. Thus, it is opportune to evaluate this world phenomenon and, certainly, in Brazil of ISO 9000 quality certification and its relation to superior financial performance of the companies. There is, in Brazil, an absence of researches related to this subject, using secondary public data, focused in publicly traded firms and using robust econometric models, to permit a certain conclusion to the brazilian context. The Akerlof-Spence approach was adopted to discuss, from the asymmetric information point of view, the adverse selection imposed to the consumers. To mitigate this, a firm should signalize its hidden attributes, creating a better image to the market and better reputation. The Akerlof-Spence approach allows to predict that, if the firms got certified, so they can search for better sales performances and, as a consequence, for better financial performances. When a firm choose to get certified, it would be signaling to the market, to its suppliers and consumers, that it has, in fact, products an services with high quality. This would allow a smaller asymmetric information and a smaller adverse selection; this also would enable a competitive advantage and would distinguish certified firms from that not certified. The certification age lasts two decades and more than 700,000 firms are certified in 161 countries around the world. Following the research line developed by two groups of researchers Terlaak and King (2006) and Corbett, Montes-Sancho and Kirsch (2005) , in this research, 207 brazilian publicly traded firms were studied for 12 years, from 1995 to 2006. There are 116 firms certified according to the 1987, 1994 and 2000 versions of ISO 9000 standard and other 91 not certified in the sample. It was employed an econometric regression model with data in static and dynamic panels, using pooled OLS, fixed effects and random effects. A non-balanced panel data with 207 firms and 2,484 observations, and a balanced panel data with 60 firms and 720 observations were assembled to research this problem. The addressed question is answered: do ISO 9000 certification permit a superior financial performance to brazilian public firms? Six hypotheses were tested, all of them related with financial performance. The six hypotheses were rejected, revealing significative results that ISO certification has a strong, direct and positive relation with financial performance of the brazilian public firms. The results of this research indicate that shareholders and managers could choose the certification as a signaling mechanism, reputation and sales growth, reduction of production costs, and improvement in ROA, ROS and ROE. ISO 9000 certification is a relevant strategic tool for competitiveness improvement.